Unsolved problems in Strong Thermal Emission Velocity Enhancement (STEVE) and the picket fence - Nishimura, Yukitoshi; Dyer, Alan; Kangas, Lauri; Donovan, Eric; Angelopoulos, Vassilis (Frontiers in Astronomy and Space Sciences, 2023)
This paper reviews key properties and major unsolved problems about strong thermal emission velocity enhancement (STEVE) and the picket fence. We firstly introduce basic characteristics of STEVE and historical observations of STEVE-like emissions particularly the case on 11 September 1891. Then we discuss major open questions about STEVE: (1) Why does STEVE preferentially occur in equinoxes? (2) How do the solar wind and storm/substorm conditions control STEVE? (3) Why is STEVE rare, despite that STEVE does not seem to require extreme driving conditions? (4) What are the multi-scale structures of STEVE? (5) What mechanisms do determine the properties of the picket fence? (6) What are the chemistry and emission mechanisms of STEVE? (7) What are the impacts of STEVE in the ionosphere-thermosphere system? And (8) what is the relation between STEVE, stable auroral red (SAR) arcs and subauroral proton aurora? These issues largely concern how STEVE is created as a unique mode of response of the subauroral magnetosphere-ionosphere-thermosphere coupling system. STEVE, SAR arcs, and proton aurora, the three major types of subauroral emissions, require energetic particle injections to the pre-midnight inner magnetosphere and interaction with cold plasma. However, it is not understood why they occur at different times, and why they can co-exist and transition from one to another. Strong electron injections into the pre-midnight sector are suggested to be important for driving the intense subauroral ion drifts (SAID). A system-level understanding about how the magnetosphere creates distinct injection features, drives subauroral flows, and disturbs the thermosphere to create the optical emissions, is required to address the key questions about STEVE. Ionosphere-thermosphere modeling that considers the extreme velocity and heating should be conducted to answer what chemical and dynamical processes occur, and how much the STEVE luminosity can be explained. Citizen scientist photographs and scientific instruments reveal evolution of fine-scale structures of STEVE and their connection to the picket fence. Photographs also show the undulation of STEVE and the localized picket fence. High-resolution observations are required to resolve fine-scale structures of STEVE and the picket fence, and such observations are important to understand underlying processes in the ionosphere and thermosphere.